An Unusual Portrait on a Drachm Attributed to Kamnaskires V - Langnas , Bob (KOINON: The International Journal of Classical Numismatic Studies, 2024)
In 2022 and 2023 hundreds of tetradrachms, drachms, and smaller silver fractions of the Elymaean king Kamnaskires V appeared on the market across many online coin stores and auction houses. All of these coins spanned the varieties of type 9.1 in Pieter Anne van’t Haaff’s Catalogue of Elymaean Coinage and types 479-484 in Numismatic Art of Persia: The Sunrise Collection, the two most recently published studies on Elymaean numismatic output. The sudden appearance of this previously rare coinage can only have resulted from one or more recent (and presumably unpublished) hoard discoveries. This article focuses primarily on a single drachm, listed as lot 344 from the Classical Numismatic Group’s Electronic Auction #532 of January/February 2023. The coin, which accompanied seven other drachms and five hemidrachms attributed to Kamnaskires V in the auction, features an off-style depiction of the king and may well be unique.